Relationships between emotional intelligence, leadership styles, organizational commitment and job performance of academic leaders at selected Malaysian research universities - Mahdinezhad, Maryam (2014)
The purpose of this study is to determine the relationship between emotional intelligence, leadership styles and job performance. The moderating role of affective commitment on the relationship between predictors and job performance was also investigated. Today’s global environment is characteristically dynamic, and complex, but there are not an exception in the academic environment. This study was designed based on the application of emotional intelligence which was classified by mixed model. The mixed model of emotional intelligence are combinations of mental resourcefulness and personal behaviors similar to being optimistic and feeling good. The second independent variable is perceived leadership styles which are reflected in transformational leadership theory (Avolio & Bass, 2002). The present study used a survey design to achieve its objectives. Simple random sampling was employed in this study. A total of 274 academic administrators were selected from selected Research Universities. This research was carried out in Universiti Putra Malaysia (UPM), Universiti Kebangsaan Malaysia (UKM), and Universiti Malaya (UM). Pearson 'r' correlation coefficients analysis was employed to determine the nature and direction of the relationship between emotional intelligence, leadership styles and job performance. The result showed that there is a significant and positive relationship between emotional intelligence and job performance (r = 0.83, p <0.001). In addition, transformational leadership style is correlated with job performance (r = 0.80, p <0.001), and transactional leadership is correlated with the job performance (r = 0.78, p <0.001). The result of multiple regressions on independent variables is that emotional intelligence, transformational leadership style, and transactional leadership style altogether predict 73% of job performance. Finally, the findings indicated that affective commitment does not have significant moderate effect on the relationship between predictors and job performance. It is recommended that to improve job performance among the academic administrators, in addition to emotional intelligence, their leadership styles should also be considered. Weak points and strong points should be investigated and the effects of factors on performance increase or decrease should be identified. Certainly, there is a need for some new and appropriate policies in order to successfully be implemented.